The Effectiveness of Boards of Directors of State Owned Enterprises in Developing Countries - Vagliasindi, Maria (World Bank, Washington, DC, 2012)
This paper aims to shed some new light on the conditions needed to ensure the effectiveness of Boards of Directors of state owned enterprises with a focus on infrastructure sectors. In the case of developing countries, empirical studies have found evidence of positive links between the composition of the Board of Directors and financial performance. Yet the lack of solid theoretical foundations, and in some cases poor data availability, makes the conclusions of most studies weak. Several policy recommendations emerge from the review of the economic literature and evidence from case studies. First, the introduction of a sufficient number of independent directors emerges as an important corporate governance milestone. Empowering them to exercise effective monitoring of management, however, may prove to be a formidable challenge for of state owned enterprises. More attention to board procedures, particularly related to the Board selection and evaluation process, is essential, to produce the necessary insulation of Boards from government interference. Ensuring sufficient continuity of services to directors is particularly crucial to improve corporate governance. In addition, other factors that may reduce directors' ability to monitor corporate activities, such as the age profile and the number of Boards on which they sit, need to be handled more carefully.